Levothyroxine Timing during Ramadan: A Randomized Clinical Trial. (10th February 2023) - Mahzari, Moeber; Al Remthi, Fahad; Ajwah, Ibrahim; Al Hazmi, Mohammed; Moafa, Wesam; Al Shahrani, Awad; Al Shehri, Sameerah; Badri, Motasim
Abstract : Introduction . Hypothyroidism requires lifelong thyroid hormone replacement with levothyroxine. For most hypothyroid patients fasting during Ramadan, compliance with the administration procedure is a challenge. This study aimed to determine the impact of different administration times of levothyroxine on thyroid-stimulating hormone (TSH) and free T4 (FT4) levels before and after the holy month of Ramadan. Materials and Methodology . Hypothyroid patients taking levothyroxine were randomized to 3 groups during Ramadan: group 1, 30 minutes before the iftar meal; group 2, 3-4 hours after the iftar meal, with no food taken for at least 1 hour after the meal; group 3, they were not given specific instructions for taking levothyroxine during Ramadan. Thyroid function tests were performed within 2 weeks before Ramadan and within 2 weeks after Ramadan. Pre- and post-Ramadan TSH and free T4 levels were compared. Mixed-effects analyzes were performed to identify factors associated with changes in TSH and FT4 levels. Results . Compliance was lower in patients taking levothyroxine 3-4 hours after iftar. In addition, the majority of patients who had not received a specific recommendation took levothyroxine 30 minutes before iftar. There was a statistically significant increase in TSH (P = 0.006 ) and FT4 (P = 0.044 ) levels after Ramadan. In multivariate analysis, the cause of hypothyroidism (Hashimoto's; postthyroidectomy; compared to postradioactive iodine) and levothyroxine dose significantly affected FT4 levels. In contrast, no variable was significantly associated with TSH level. The timing of levothyroxine intake during Ramadan did not significantly affect TSH or FT4 levels. Conclusion . TSH and FT4 significantly increased after Ramadan. However, the timing of levothyroxine intake per se had no influence on TSH or free T4 levels. Therefore, hypothyroid patients might take levothyroxine either 30 minutes or 3-4 hours after iftar with no meal for 1 hour, depending on preference.